2020
DOI: 10.1109/access.2020.3028127
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Similarities of Big Data Projects–A Use Case Driven Approach

Abstract: Big data is considered as one of the most promising technological advancements in the last decades. Today it is used for a multitude of data intensive projects in various domains and also serves as the technical foundation for other recent trends in the computer science domain. However, the complexity of its implementation and utilization renders its adoption a sophisticated endeavor. For this reason, it is not surprising that potential users are often overwhelmed and tend to rely on existing guidelines and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
(271 reference statements)
0
5
0
Order By: Relevance
“…BD reflects the interactions among employees and customers stored in the system of the organization, which eventually furnishes actionable, predictive, descriptive as well as prescriptive outcomes [5,6]. Because of the high volume of BD, in the form of high velocity and various information assets, valuable knowledge and information extraction from it remains full of complexity [7].…”
Section: Introductionmentioning
confidence: 99%
“…BD reflects the interactions among employees and customers stored in the system of the organization, which eventually furnishes actionable, predictive, descriptive as well as prescriptive outcomes [5,6]. Because of the high volume of BD, in the form of high velocity and various information assets, valuable knowledge and information extraction from it remains full of complexity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, BD reflects interactions between employees, consumers, suppliers, and distributors of products (goods or services), which often provide descriptive and predictive results (Shirdastian et al, 2019 ; Baig et al, 2021 ), which drastically transform the competitiveness of firms, depending on the acquisition of timely information to achieve higher levels of performance (Gonzales et al, 2015 ; Volk et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of BD as a solid foundation for performance improvement has been established in Coleman et al ( 2016 ); Akter et al ( 2017 ); Mikalef et al ( 2019 ); Almaiah and Nasereddin ( 2020 ), and Dubey et al ( 2020 ) and most of these studies indicated a favorable association between DB success and business performance. However, due to the large size of the database, obtaining important information and insights remains a challenge (Volk et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Big data represent the interactions between employees and consumers recorded in an organisation's system, providing actionable, predictive, descriptive, and prescriptive results [6]. Owing to the large amount of big data in a state of high rapidity and the diversity of information assets, extracting meaningful information and knowledge remains challenging [7,8].…”
Section: Introductionmentioning
confidence: 99%